After treat-to-target: can a targeted ultrasound initiative improve RA outcomes?. Issue 1042 (19th July 2012) - Wakefield, Richard J; D'Agostino, Maria Antonietta; Naredo, Esperanza; Buch, Maya H; Iagnocco, Annamaria; Terslev, Lene; Ostergaard, Mikkel; Backhaus, Marina; Grassi, Walter; Dougados, Maxime; Burmester, Gerd R; Saleem, Benazir; et al.
Abstract : For patients with rheumatoid arthritis (RA), remission can be achieved with tight control of inflammation and early use of disease modifying agents. The importance of remission as an outcome has been recently highlighted by European League Against Rheumatism recommendations. However, remission when defined by clinical remission criteria (disease activity score, simplified disease activity index, etc) does not always equate to the complete absence of inflammation as measured by new sensitive imaging techniques such as ultrasound (US) . There is evidence that imaging synovitis is frequently found in these patients and associated with adverse clinical and functional outcomes. This article reviews the data regarding remission, ultrasound imaging and outcomes in patients with RA to provide the background to a consensus statement from an international collaboration of ultrasonographers and rheumatologists who have recently formed a research network - the Targeted Ultrasound Initiative (TUI) group. The statement proposes that targeting therapy to PD activity provides superior outcomes compared with treating to clinical targets alone and introduces the rationale for a new randomised trial using targeted ultrasound in RA.